MicroRNAs 29, 150, 155, 223 level and their relation to viral and immunological markers in HIV-1 infected naive patients. (2nd August 2018) - Moghoofei, Mohsen; Bokharaei-Salim, Farah; Esghaei, Maryam; Keyvani, Hossein; Honardoost, Maryam; Mostafaei, Shayan; Ghasemi, Amir; Tavakoli, Ahmad; Javanmard, Davod; Babaei, Farhad; Garshasbi, Saba; Monavari, Seyed Hamidreza
Aim: The aim of this study was to assess the relationship between microRNAs and viral and immunological markers in HIV-1 infection.Materials & methods: The expression level of miRNAs was evaluated in 60 HIV-1 patients and 20 healthy controls using real-time PCR assays.Results: The results showed that among all miRNAs, miR-29 and miR-150 were significantly downregulated in HIV-1 patients compared with healthy controls, while miR-155 and miR-223 were significantly upregulated compared with healthy controls (p < 0.001 for all comparisons).Conclusion: The mentioned miRNAs seem to influence the clinical progression of HIV-1 infection in naive patients. Moreover, determining the profiles of miRNAs involved in the pathogenesis of HIV infection and manipulating these miRNAs could lead to opening a new gate to HIV-1 infection control.